2016
DOI: 10.1039/c6gc01826b
|View full text |Cite
|
Sign up to set email alerts
|

Acid-catalysed carboxymethylation, methylation and dehydration of alcohols and phenols with dimethyl carbonate under mild conditions

Abstract: Dimethyl carbonate (DMC) chemistry has been extended to include acid-catalysed reactions of different aliphatic alcohols and phenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
39
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 51 publications
3
39
0
1
Order By: Relevance
“…The chemical catalysis is faster than the enzymatic process. Among the different kinds of chemical catalysis, alkaline catalysis has been widely employed in DMC-mediated biofuels and chemicals production [34,41,66,69,78]. The cost of alkaline catalysts, such as metal hydroxides, alkoxides and metal oxides, is comparatively cheaper than enzyme, and high yields have been obtained with chemical catalysis [59].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The chemical catalysis is faster than the enzymatic process. Among the different kinds of chemical catalysis, alkaline catalysis has been widely employed in DMC-mediated biofuels and chemicals production [34,41,66,69,78]. The cost of alkaline catalysts, such as metal hydroxides, alkoxides and metal oxides, is comparatively cheaper than enzyme, and high yields have been obtained with chemical catalysis [59].…”
Section: Discussionmentioning
confidence: 99%
“…Brønsted and Lewis acids were used in DMC-mediated carboxymethylation and methylation with various alcohols and phenols [66]. Deshmukh et al [67] reported that the use of Brønsted and Lewis acidic ionic liquids enhanced the yield of diphenyl carbonate (DPC) synthesis.…”
Section: Chemical Process For Dmc-based Chemicals Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly from solvent screening studies, dimethyl carbonate was found to be the best alternative for dichloromethane and the most of the solvents were compatible solvents for the reaction except polar solvents such as water, DMSO, DMF and MeOH (entries 5-20). Further, elevating the reaction temperature increased the reaction rate with complete conversion (entries [18][19][20]. The FeCl 3 catalyst furnished a complete and clean conversion within 6 h at 90 C in dimethyl carbonate (99%, entry 20) and no traces of aldimine intermediate 3a were found in the reaction mixture.…”
mentioning
confidence: 99%
“…In the case of aldehyde substrate containing a hydroxy group, under the optimized reaction conditions, the methoxycarbonylated product 4ad 0 was obtained in 96% yield instead of the expected product 4ad. 18 To overcome this particular substrate issue, switching solvent system to propylene carbonate afforded the desired product 4ad in 94% yield. Next, we examined the scope of aldehydes with 2-methyl-1,1-diphenylhomoallylamine (2b).…”
mentioning
confidence: 99%